Dynamic Spatial Tuning Patterns of Shoulder Muscles with Volunteers in a Driving Posture - Fice, Jason B.; Larsson, Emma; Davidsson, Johan (Frontiers in Bioengineering and Biotechnology, 2021)
Human body models (HBMs) of drivers for pre-crash simulations need active shoulder muscle control and volunteer data is lacking. The goal of this paper was to build shoulder muscle dynamic spatial tunning curves, with a secondary focus to present shoulder kinematic evaluation data. 8M and 9F volunteers sat in a driver posture, with their torso restrained, and were exposed to upper arm dynamic perturbations in 8 directions perpendicular to the humerus. A dropping 8 kg weight connected to the elbow through pullies applied the loads; the exact timing and direction were unknown. Activity in 11 shoulder muscles was measured using surface electrodes, and upper arm kinematics were measured with three cameras. We found directionally specific muscle activity and presented dynamic spatial tuning curves for each muscle separated by sex. The preferred directions were similar between males and females, with the largest difference of 31° in the pectoralis major muscle. Males and females had similar elbow displacements, with maximums of 189 ± 36 mm for males in flexion and 196 ± 36 mm in adduction for females. The data presented here can be used to design shoulder muscle controllers and evaluate the performance of the shoulder in HBMs.